Hippocampal Transcriptome Changes After Subarachnoid Hemorrhage in Mice - Regnier-Golanov, Angelique S.; Dündar, Friederike; Zumbo, Paul; Betel, Doron; Hernandez, Magda S.; Peterson, Leif E.; Lo, Eng H.; Golanov, Eugene V.; Britz, Gavin W. (Frontiers in Neurology, 2021)
After subarachnoid hemorrhage (SAH), up to 95% of surviving patients suffer from post-SAH syndrome, which includes cognitive deficits with impaired memory, executive functions and emotional disturbances. Although these long-term cognitive deficits are thought to result from damage to temporomesial-hippocampal areas, the underlying mechanisms remain unknown. To fill this gap in knowledge, we performed a systematic RNA sequencing screen of the hippocampus in a mouse model of SAH. SAH was induced by perforation of the circle of Willis in mice. Four days later, hippocampal RNA was obtained from SAH and control (sham perforation) mice. Next-generation RNA sequencing was used to determine differentially expressed genes in the whole bilateral hippocampi remote from the SAH bleeding site. Functional analyses and clustering tools were used to define molecular pathways. Differential gene expression analysis detected 642 upregulated and 398 down-regulated genes (false discovery rate <0.10) in SAH compared to Control group. Functional analyses using IPA suite, Gene Ontology terms, REACTOME pathways, and MsigDB Hallmark gene set collections revealed suppression of oligodendrocytes/myelin related genes, and overexpression of genes related to complement system along with genes associated with innate and adaptive immunity, and extracellular matrix reorganization. Interferon regulatory factors, TGF-β1 and BMP were identified as major orchestrating elements in the hippocampal tissue response. The MEME-Suite identified binding motifs of Krüppel-like factors, zinc finger transcription factors, and interferon regulatory factors as overrepresented DNA promoter motifs. This study provides the first systematic gene and pathway database of the hippocampal response after SAH. Our findings suggest that damage of the entorhinal cortex by subarachnoid blood may remotely trigger specific hippocampal responses, which include suppression of oligodendrocyte function. Identification of these novel pathways may allow for development of new therapeutic approaches for post-SAH cognitive deficits.